Mechanical on-chip microwave circulator. Issue 1 (December 2017) - Barzanjeh, S.; Wulf, M.; Peruzzo, M.; Kalaee, M.; Dieterle, P.; Painter, O.; Fink, J.
Abstract Nonreciprocal circuit elements form an integral part of modern measurement and communication systems. Mathematically they require breaking of time-reversal symmetry, typically achieved using magnetic materials and more recently using the quantum Hall effect, parametric permittivity modulation or Josephson nonlinearities. Here we demonstrate an on-chip magnetic-free circulator based on reservoir-engineered electromechanic interactions. Directional circulation is achieved with controlled phase-sensitive interference of six distinct electro-mechanical signal conversion paths. The presented circulator is compact, its silicon-on-insulator platform is compatible with both superconducting qubits and silicon photonics, and its noise performance is close to the quantum limit. With a high dynamic range, a tunable bandwidth of up to 30 MHz and an in situ reconfigurability as beam splitter or wavelength converter, it could pave the way for superconducting qubit processors with multiplexed on-chip signal processing and readout. Nonreciprocal optical elements often require magnetic materials in order to break time-reversal symmetry. Here, Barzanjeh et al. demonstrate a magnetic-free on-chip microwave circulator that utilizes the interference from six electro-mechanical signal paths.